Cell-Free Epstein–Barr Viral Loads in Childhood Hodgkin Lymphoma: A Study from South India. (1st September 2013) - Sinha, Mahua; Rao, C.R.; Shafiulla, M.; Appaji, L.; BS, Aruna Kumari; Sumati, B.G.; Avinash, T.; Jayshree, R.S.
<x xml:space="preserve">Abstract</x> Cell-free Epstein–Barr viral (EBV) DNA is detectable in plasma of patients with EBV-related lymphomas. The aim of this study was to evaluate the utility of plasma EBV DNA as a biomarker of EBV association in childhood Hodgkin lymphoma (HL). Furthermore, an attempt was made to evaluate the effectiveness of viral quantitation for assessing response to chemotherapy. Thirteen cases of childhood HL were included in this study. All 13 cases were EBV associated as reflected by expression of EBV LMP1 in the tumor specimen. Eighty-five percent had detectable EBV DNA levels; viral loads ranging from 2.9 to156.2 × 103 copies/ml (mean 29 × 103 copies/ml); while in 2 patients and 30 controls tested, viral DNA was undetectable. In four patients, follow-up samples were available after three cycles of chemotherapy; all had EBV DNAemia prior to chemotherapy but undetectable EBV DNA posttherapy. This corroborated with complete response in these four patients. Plasma EBV viral load quantification maybe a useful tool for detecting EBV association with lymphomas and in monitoring response to treatment in childhood HL in centers with limited resources, more so in India where majority of childhood HL is likely to be EBV associated. This is the first Indian study estimating plasma EBV viral loads in HL.